The Effect of Leverage, Firm Size, and Asset Turnover on Revenue Growth in Automotive Sector Companies Listed on the Indonesia Stock Exchange for the 2020–2024 Period - Muhammad Baihaqi; Fithri Dzikrayah; Iman Supratman (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The COVID-19 pandemic caused a drastic decline in vehicle sales in Indonesia by 48.5% in 2020, accompanied by technological transformation towards electrification that required automotive companies to adapt quickly. This study analyzes the effect of leverage, firm size, and asset turnover on revenue growth in six automotive companies listed on the Indonesia Stock Exchange for the period 2020-2024. Using panel data regression analysis with a Fixed Effects Model, this study found that leverage had no significant effect (coefficient = -0.001312; p = 0.9008), while firm size (coefficient = 0.990886; p = 0.0000) and asset turnover (coefficient = 1.106046; p = 0.0000) had a positive and highly significant effect on revenue growth. Simultaneously, all three variables have a significant effect with an R-squared of 99.57% (F-statistic 607.4727; p=0.0000). These findings indicate that operational efficiency and business scale are key determinants of revenue growth for automotive companies amid industry disruption.